Receptors and ligands involved in viral induction of type I interferon production by plasmacytoid dendritic cells. - Seeds, R; Gordon, S; Miller, J (2006)
Virus infection is sensed by the innate immune system which then rapidly initiates biosynthesis of type I interferon (IFN). The IFN signaling systems produce a broadly effective innate antiviral response by creating an antiviral state in both an autocrine and paracrine manner in cells and by activating innate and adaptive immunity. Plasmacytoid dendritic cells (pDCs) have the unique ability to produce very high levels of type I IFN following viral infection in vivo. Most recent research has focused on oligonucleotide-mediated induction of type I IFN production, implicating viral genome and replication intermediates as the stimulus for this response. However there are additional viral ligands which can potentially induce type I IFN production in pDCs, such as envelope glycoproteins, viral glycolipids, tegument, capsid or nuclear proteins. This area of viral immunology, which has been neglected in the literature, will be discussed here.